MUNICIPAL BONDS AS THE FINANCING STRATEGY FOR URBAN INFRASTRUCTURE : CASE STUDY OF JAKARTA MRT - Eko Nur Surachman; Hadi Setiawan (Jurnal Keuangan dan Perbankan, 2016)
The construction of Jakarta MRT Phase I has been carried out by using funds from foreign debt. Meanwhile, Jakarta MRT Phase II or other local infrastructure projects are still waiting for new funding scheme. One alternative is municipal bonds. This study investigate the possibilities of using municipal bonds to finance urban infrastructure project with the case study of Jakarta MRTPhase I. The analyzed use three perspectives including financial aspect, legal aspect, and Jakarta financial capacity aspect. financial analysis using discounted cash flow (DCF), net present value (NPV) and internal rate of return (IRR).Secondly, study literature is used in the legal analysis by exploring specific regulations regarding the municipal bonds. Finally, the Jakarta Regional Budget and Jakarta Budget Audit Report is examined to get insight and depth information regarding its financial capacity. The result is municipal bonds are feasible as the source of financing Jakarta MRT Project.